SOCORRO! (CIPEEX, 2024)
The “Socorro!” app aims to help the user when he needs it most, when it is necessary to useemergency numbers to solve problems. The focus on security applied to the user, who willuse the application in cases of need through external force, was widely discussed, sincethere are similar solutions on the market, but none specifically counts with all the emergencynumbers existing at the national level, based on in this, an application model was prototyped,capable of responding to this need, where the interface will be summarized in a button andthe information referring to the user will be previously filled and at the time of use, sent to thecompetent authority. On the creation of this application, we sought to analyze the existingmodels of solutions for user safety, as well as the response time of the authorities or thoseresponsible for solving the problem in question, starting from the user's call for assistance.One of the main points raised was the focus on the user experience, since the applicationmust be used in emergency situations, it must be simple and minimalist, but effective andreliable. Some methodologies were used to map users, as well as to define the application'suser interface. Methods such as Design Thinking, Color Theory and Creation of personasbecame essential for the success of the creation of MVPS, which will be used for testing andvalidation of the project. The application uses as a premise the Doherty’s Threshold Laws,which concerns the speed within the product and establishes an international standard of 0.4seconds of application response, and the Hick-Hymann’s Law, which is responsible for theneed for ease in the interface of an application. With the combination of these laws, it ispossible to guarantee that the application will be fast, minimalist and easy to understand forthe user.
Keywords: Desing Thinking; Color Theory; Personas; Hick-Hymann; Doherty